Liderazgo transformacional y clima organizacional de las instituciones educativas de la Ciudad Satélite Santa Rosa - Región Callao - Morocho Cáceres, Luz Marina (2010)
This research aimed to establish the existence of relation between leadership style and organizational environment in the city’s School in Satellite City Santa Rosa, Callao Region. The variables investigated were Transformational Leadership and Organizational Environment (dimensions institutional identity, interpersonal relations and institutional dynamics.) The research was descriptive and correlational design. We worked with a population consisting of 103 teachers, managing instruments transformational leadership scales of Segovia (2001), and the scale of organizational climate of Berrocal (2006), possessing both the validity and reliability tools appropriate to the context worked.The study showed findings allowed to conclude the existence of significant correlation between transformational leadership and organizational environment and dimensions, institutional identity, interpersonal relations and institutional dynamics of organizational environment to a significance level of 0.001.